A Composite Multiple-based Stock Valuation Model - Lau, Mudita; Widyarini, Maria; Faisal, Achmad (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2025)
This study seeks to examine whether a composite valuation model (made of several multiples) can outperform a single-multiple valuation model in valuation accuracy. This study applied a trial-and-error iteration using scripts written in R studio to optimize the weight of each multiple in each composite, aiming to reach a minimum valuation error for each composite valuation model. Based on financial data of 2009-2019, a composite valuation model performs better than a single-multiple valuation model in assessing all peer groups, achieving up to 18% greater accuracy, which is a significant improvement. The result suggests that a composite valuation model generally offers superior valuation accuracy. Academics and institutional investors searching for improved valuation accuracy may consider a composite valuation model as an alternative method. This study adds empirical evidence to the current knowledge on multiple-based valuation models, highlighting the potential advantages of a composite valuation model over a single-multiple model.